Penggunaan Demulsifier pada Heavy Crude Oil Suko Barat Distrik PT Pertamina Hulu Rokan Regional 1 Zona 1 Jambi Field - Yuliani, Aliyah; Hasan, Abu; Yuliati, Selastia (Jurnal Teknologi Riset Terapan, 2024)
Purpose: The Final Report that will be carried out has the following objectives: Getting demulsifier injection optimization results Getting the best %BS&W results at PT Pertamina Hulu Rokan Regional 1 Zone 1 Jambi Field. Research methodology: The research was carried out at the PT EiON Cheimiicals Putra Laboratory. The research time is estimated to last 1 month. Literature research was carried out by extracting information via the internet and scientific journals. Results: In this study, the best operating conditions were obtained at 60 temperatures, 60 minutes of residence time and a demulsifier concentration of 40 ppm resulting in a %BS&W of 0.3%. . Conclusion: The crude oil purification used a demulsifier, analyzing water drop, dosage, and BS&W percentage. The best result was 0.3% BS&W at 60, 60 minutes, and 40 ppm, meeting the quality standard of below 1%. Limitations: The limitations of this study are  that the test was carried out under laboratory conditions so that the results may differ in the field, Parameters are limited in injection time, demulsifier concentration, and temperature; other factors have not been analyzed, The duration of the study is limited so that the long-term effects have not been measured. Contribution: This research can be useful for companies that produce heavy crude oil such as PT Pertamina Hulu Rokan Zone 1 Regional 1 Jambi Field which produces good oil quality.